Focal Mechanism and Seismogenic Structure of the MS 5.1 Qingbaijiang Earthquake on February 3, 2020, Southwestern China - Zhao, Min; Long, Feng; Yi, Guixi; Liang, MingJian; Xie, Jiangtao; Wang, Siwei (Frontiers in Earth Science, 2021)
The 3 February 2020 MS 5.1 Qingbaijiang earthquake, southwestern China, is the closest recorded MS ≥ 5.0 event to downtown Chengdu City to date, with an epicentral distance of only 38 km. Here we analyze seismic data from the Sichuan and Chengdu regional seismic networks, and employ a multi-stage location method to relocate the earthquakes that have occurred along the central and northern segments of the Longquanshan fault zone since 2009, including the MS 5.1 Qingbaijiang earthquake sequence, to investigate the seismogenic structure of the region. The relocation results indicate that the seismicity along the central and northern segments of the Longquanshan fault zone has occurred mainly along the eastern branch since 2009, with the hypocentral distribution along a vertical cross-section illustrating a steep, NW-dipping parallel imbricate structure. The terminating depth of the eastern branch is about 12 km. The distribution of the MS 5.1 Qingbaijiang earthquake sequence is along the NE–SW-striking Longquanshan fault zone. The aftershock focal depths are in the 3–6 km range, with the mainshock located at 104.475°E, 30.73°N. Its initial rupture depth of 5.2 km indicates that the earthquake occurred above the shallow decollement layer of the upper crust in this region. The hypocentral distribution along the long axis of the aftershock area highlights that this earthquake sequence occurred along a fault dipping at 56° to the NW. Our surface projection of the inferred fault plane places it near the eastern branch of the Longquanshan fault zone. We infer the MS 5.1 mainshock to be a thrust faulting event based on the focal mechanism solution via the cut-and-paste waveform inversion method, with strike/dip/rake parameters of 22°/36°/91° and 200°/54°/89° obtained for nodal planes I and II, respectively. We identify that the seismogenic fault of the MS 5.1 Qingbaijiang earthquake lies along the eastern branch of the Longquanshan fault zone, and nodal plane II represents the coseismic rupture plane, based on a joint analysis of the event relocation results, mainshock focal mechanism, and regional geological information. Our study provides vital information for assessing the seismic hazard of the Longquanshan fault zone near Chengdu City.